Green perception and behavior among students at UiTM Melaka / Siti Norashikin Bashirun ... [et al.] - Siti Norashikin Bashirun, Bashirun; NurIdayu, Badrolhisham; Farah Shazlin, Johari; NurhafizahMohd, Zolkapli; Nor MasliaRasli, Samudin; Nur Faithzah, Jamian (2015)
This study examined how student at UiTM Bandaraya Melaka perceived green practices. A convenient sample of 200 respondents was surveyed. Students have positive perception towards green and findings show there is no significant difference on perception and there is significant difference in doing green activity. Result indicated that “recycle paper” is the most chosen activity done by respondents whereas “attending green conference” is the least activity respondent chose to get involve. The implications of this study are useful to student’s association, university and environmental organization as a guideline to organize green activities and to motivate students to participate actively in doing green activities.